2014
DOI: 10.1165/rcmb.2013-0374oc
|View full text |Cite
|
Sign up to set email alerts
|

The Aquaporin 1 C-Terminal Tail Is Required for Migration and Growth of Pulmonary Arterial Myocytes

Abstract: Pulmonary arterial smooth muscle cell (PASMC) proliferation and migration are important contributors to the vascular remodeling that occurs during development of pulmonary hypertension. We previously demonstrated that aquaporin (AQP)1, a member of the water channel family of proteins, was expressed in PASMCs and was necessary for hypoxia-induced migration; however, the mechanism by which AQP1 controls this response is unclear. The C-terminal tail of AQP1 contains putative calcium (EF-hand) and protein binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 37 publications
3
28
0
Order By: Relevance
“…In detail, rat pulmonary artery smooth muscle cells exposed to hypoxia selectively increased AQP1 protein levels and, in turn, migration. Silencing of AQP1 via siRNA prevented the hypoxia-induced migration in these cells [13,14]. Our initial experiments confirmed these findings by showing that the levels of AQP1 are increased by hypoxia in pulmonary artery smooth muscle cells.…”
Section: Discussionsupporting
confidence: 77%
“…In detail, rat pulmonary artery smooth muscle cells exposed to hypoxia selectively increased AQP1 protein levels and, in turn, migration. Silencing of AQP1 via siRNA prevented the hypoxia-induced migration in these cells [13,14]. Our initial experiments confirmed these findings by showing that the levels of AQP1 are increased by hypoxia in pulmonary artery smooth muscle cells.…”
Section: Discussionsupporting
confidence: 77%
“…43 Direct effects of hypoxia on PASMCs are also likely to play a role in vascular remodeling. For example, cells exposed to hypoxia ex vivo or derived from chronically hypoxic animals exhibit increases in both migration and proliferation, [53][54][55][56] and both K + channel activity and [Ca 2+ ] i are likely to play a role. Agents that activate and/or increase expression of K + channels, including the steroid hormone dehydroepiandrosterone and the metabolic modulator dichloroacetate, reduced remodeling in chronically hypoxic rats, 46,57,58 likely because increased intracellular K + confers resistance to apoptosis.…”
Section: Mechanisms Of Hph: Lessons From Animal Modelsmentioning
confidence: 99%
“…AQP1 has been shown to facilitate cell migration (7), cell proliferation (8), and angiogenesis (9). One recent study found an interaction between AQP1 and b-catenin, a transcription cofactor with T-cell factor/lymphoid enhancer factor (TCF/LEF) in the Wnt signal pathway.…”
mentioning
confidence: 99%